Recontextualizing the Interpretation of the Word "Kafir" in Surat Al-Maidah Verse 44 for Sustainable Peace in Indonesia - Ramadlani, Muhammad Tsalis; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to examine the nature of kufr in Islam, explore the understanding of the word "kafir" in Surah Al-Maidah, and compare the views of the ulama with those of the Khawarij. With the historical background of the first schism in the Muslim community during Uthman's caliphate, the emergence of the Khawarij group, and the impact of extremism such as terrorist attacks in Indonesia, this research is relevant to understanding the mindset and beliefs of Khawarij. The results of this study indicate that acts of terror that threaten security stability, carried out by some Muslims, stem from the understanding of Khawarij and their mistakes in understanding the word kafir, especially in Surah Al-Maidah Verse 44. The research method used is qualitative with a literature study approach to analyze various sources of literature and previous research. The results of the study are expected to provide insight into the understanding of kufr in Islam and the potential differences in interpretation related to the word kafir in Surah Al-Maidah so as to reduce the takfiri paradigm in Indonesia which leads to sustainable security stability.